EFEKTIFITAS PROGRAM SOSIAL BANK INDONESIA (PSBI) TERHADAP UMKM DI KOTA PALEMBANG - Ritawati, Ritawati Ritawati (I-Economics, 2015)
The empowerment of The Small-Medium Enterprises sectors becomes crusial, due to the fact its sectors was supporting the objectives and the realization of socio economic development of the majority of Indonesian peoples.  It’s development has a big contribution to the Indonesian economics. Realized the potentiality of The Small-Medium Enterprises sectors in Palembang, Bank Indonesia with his Social Program build the linkage between the BI and the small-medium enterprises business.  Finally this reasearch finds out that Social Program of Bank Indonesa in cooperation with The Small-Medium Enterprises has been contributed to the socio economics development of the small-medium enterprises in Palembang. Key Words: The Small-Medium Enterprises, Social Program, and Bank Indonesia